Sekularisme, die Gees van Ons Tyd – ’n Bedreiging I - van der Walt, B. J. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2004)
This article (the first in a series of three) is an effort to describe our contemporary secular age in order for us to be able to understand it better and to know how to act as Chri tians. To achieve this aim, attention is given to the following: (1) As an introduction the phrase “the spirit of our time” is explained. (2) Then the question is discussed why secularism only recently became a fact in South Africa and its main features are mentioned. (3) This is followed by a brief description of a much more advanced form of secularism in a country like the Netherlands. After been enriched by the ideas of others in the first article, the second article presents the author's own philosophical characterization of secularism as well as an explanation why secularism is such a great threat to Christianity. In the third (final) article, an in-depth analysis will be made of the secularist distinction between private and public and its consequences for Christian education in the light of a Christian philosophy of society.